Institutional and Policy Analysis of River Basin Management : The Alto-Tietê River Basin, São Paulo, Brazil - Johnsson, Rosa Maria Formiga; Kemper, Karin Erika (World Bank, Washington, DC, 2012)
The authors describe and analyze river basin management in the most intensely urbanized and industrialized region of Brazil. The area covered by the Alto Tiete basin is almost coterminous with the Metropolitan Region of Sao Paulo. With a drainage area of 5,985 square kilometers (2.4 percent of the state's territory), the basin encompasses 35 of the 39 municipalities and 99.5 percent of the population of Greater Sao Paulo. Population growth and urban sprawl in Greater Sao Paulo have been rapid and uncontrolled in recent decades. In 2000, 17.8 million people lived in the basin and by 2010 the population is estimated to reach 20 million. This massive human occupation was accompanied by the large-scale construction of water infrastructure, including dams, pumping stations, canals, tunnels, and inter-basin transfers to and from neighboring basins. Today, the Alto-Tiete basin is served by a complex hydraulic and hydrological system. Despite this extensive water infrastructure, the water availability of the region is still very low (201